2000
DOI: 10.1111/j.1469-445x.2000.01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of HOE642, a Selective Blocker of Na+‐H+ Exchange, Against the Development of Rigor Contracture in Rat Ventricular Myocytes

Abstract: The objective of this study was to investigate the effect of Na+‐H+ exchange (NHE) and HCO3−‐Na+ symport inhibition on the development of rigor contracture. Freshly isolated adult rat cardiomyocytes were subjected to 60 min metabolic inhibition (MI) and 5 min re‐energization (Rx). The effects of perfusion of HCO3− or HCO3−‐free buffer with or without the NHE inhibitor HOE642 (7 μM) were investigated during MI and Rx. In HCO3−‐free conditions, HOE642 reduced the percentage of cells developing rigor during MI fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Slowed ATP depletion during ischemic conditions. The present observations in cultured cardiomyocytes exposed to simulated ischemia and in intact myocardium submitted to zero-flow ischemia are in agreement with previous studies showing that NHE inhibition slows-down the rate of ATP depletion during ischemia and delays the onset of rigor contracture (6,11,25). Moreover, in the present study, modulation of the rate of ATP depletion during ischemia by modifying myocardial temperature within the physiological range (35.5-38.5°C) allowed us to evaluate the contribution of the effect of cariporide on ATP content to its protective effect against ischemia-reperfusion injury.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Slowed ATP depletion during ischemic conditions. The present observations in cultured cardiomyocytes exposed to simulated ischemia and in intact myocardium submitted to zero-flow ischemia are in agreement with previous studies showing that NHE inhibition slows-down the rate of ATP depletion during ischemia and delays the onset of rigor contracture (6,11,25). Moreover, in the present study, modulation of the rate of ATP depletion during ischemia by modifying myocardial temperature within the physiological range (35.5-38.5°C) allowed us to evaluate the contribution of the effect of cariporide on ATP content to its protective effect against ischemia-reperfusion injury.…”
Section: Discussionsupporting
confidence: 81%
“…In a recent study (31), pretreatment with the selective NHE inhibitor SM-20550 was associated with attenuated Ca 2ϩ overload in mitochondria obtained from rat hearts submitted to 40 min of ischemia and 20 min of reperfusion, a result in agreement with the protective effect of NHE inhibition against cell necrosis secondary to ischemia-reperfusion, but [Ca 2ϩ ] m during ischemia was not measured. Our observation that cariporide, at concentrations that have been consistently found cardioprotective in isolated cells (25,27) and intact myocardium in vivo (6,16), enhanced mitochondrial Ca 2ϩ accumulation during simulated ischemia may appear surprising. Although increased [Ca 2ϩ ] m has been shown to have detrimental effects (4), there is a lack of information on the consequences of mitochondrial Ca 2ϩ overload during ischemia.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The effectiveness of both interventions has been solidly established. Several studies have shown that extracellular acidosis delays ATP depletion (21,29,38). However, because acidosis markedly decreases conductivity of both gap junctions and hemichannels (membrane pores formed by connexins) (1,34), the question can be raised regarding whether the changes in sarcolemmal permeability and tissue electrical resistance observed late during prolonged ischemia reflect a fast opening of hemichannels, and the protective effect of acidosis is due to interference with this phenomenon.…”
Section: Protective Effects Of Acidosis and Glycinementioning
confidence: 96%
“…The time course of cell death in hypoxic hearts was determined by monitoring LDH release in the coronary effluent. The studies were also performed under conditions that are known to modify the progression of hypoxic injury as acidification of the hypoxic buffer (21,29,38) or addition of glycine (12,20). The effects of these interventions on sarcolemmal rupture during energy depletion were confirmed in a cell line derived from murine cardiac myocytes (HL-1).…”
mentioning
confidence: 98%